Design of Stimulated Raman Scattering -Aware Routing Wavelength Assignment Algorithm - Sim, Wai Seng (2016)
There has been an intensive on-going research on physical impairments in RWA algorithm in WDM optical networks. Some physical impairment that has been studied includes Polarization-mode Dispersion (PMD), Amplified Spontaneous Emission (ASE), Four-wave mixing (FWM) and Stimulated Raman Scattering (SRS) and etc. There are various physical impairment-aware RWA approaches proposed in the literature, but SRS-aware RWA approach has not been proposed . The aim of this research is to propose a SRS-aware RWA algorithm and evaluate its performance in different network.